Dentinal Defects Induced by Offset and Alternating Contact Endodontic Rotary Files: An In Vitro Study - Abeer A Abass; Haidar T Fadhil; Firas S. O Albaaj (Wolters Kluwer Medknow Publications, 2022)
Objective: Dentinal defects during root canal preparation could lead to treatment failure and tooth extraction. Many rotary files are manufactured with asymmetric cross sections or alternating cutting edges to minimize contact with the canal wall. Decreasing contacts may generate low stresses and, hence, fewer dental defects during root canal instrumentation. This study aimed to evaluate the incidence of dentinal defects induced by ProTaper Next, Wave One Gold (Dentsply Maillefer, Ballaigues, Switzerland), and iRace (FKG Dentaire SA, La Chaux-de-Fonds, Switzerland) in comparison to the symmetric file HyFlex CM (Coltene-Whaledent, Allstetten, Switzerland). Materials and Methods: Sixty extracted single-rooted premolars with round canals were selected for this study. All teeth were decoronated and divided into four experimental groups according to the tested file systems. In each group, 15 canals were prepared with the crown down technique using a speed and torque recommended by manufacturers. The root samples were then sectioned horizontally at 3, 6, and 9 mm from the apex and examined under a stereomicroscope to evaluate the presence or absence of dentinal defects. Data were statistically analyzed with SPSS software using a chi-square test. Results: Dentinal defects were observed at all canal levels following all methods of instrumentation. ProTaper Next showed the lowest values of dentinal defects, whereas Hyflex CM displayed the highest values. Conclusion: Files with few contacts with the canal wall decreased the number of dentinal defects compared to the HyFlex CM file, with a nonsignificant difference being observed.